Ensino de ortografia da língua portuguesa para uma aluna falante de português e espanhol: estudo de caso - Schroder, Maristela Krause (2020)
This paper presents a pedagogical intervention aimed at teaching orthography to a third year elementary school student, who speaks Portuguese and Spanish, in the context of a municipal school in Foz do Iguaçu, on the border with Paraguay and Argentina, countries where Spanish is the official language. The work aims to better understand the teaching of orthography to bilingual students, speaking both Portuguese and Spanish. It assumes that the distinction between speech and writing, and the different pronunciations can affect the learning of orthography. The written language is more rigid and static due to the need to preserve the standards of the written models, hence the importance of teaching orthography to enable different people, from different times and places, to be able to use and understand it. The qualitative methodology was adopted, based on historical-cultural theory and linguistics applied to literacy. Individualized pedagogical interventions and observations as methodological tools were used. It is concluded that ludic activities, based on the recognition of linguistic varieties and their particularities, helped the student to understand the contradictions between speech and writing.